Effect of concept mapping education on clinical decision-making in nursing students: A randomized controlled trial - Mahla Doustinouri; Fatemeh Sadeghy; Fatemeh Hatefi; Fereshteh Mallahigar; Seyyedeh Mahdiyeh Khastar (Journal of Nursing Advances in Clinical Sciences)
Clinical decision-making is a critical and essential skill in clinical care. Nurses' proficiency in proper clinical decision-making significantly improves the quality of nursing care. As an active learning approach, concept mapping education plays a vital role in deep learning and applying critical thinking skills in clinical decision-making. This study aimed to investigate the impact of concept mapping on clinical decision-making in nursing students. The study was an experimental design with two groups, where participants were randomly assigned to the test group (25 students) or the control group (25 students). Data were collected using the clinical decision-making questionnaire. Based on relevant literature, the test group participated in eight concept mapping sessions lasting 60 to 90 minutes each, while the control group received traditional lecture-based education. Covariance analysis, excluding the effect of the pre-test, showed no significant difference (P=0.86, eta=0.01). Still, a paired t-test revealed a significant difference in the test group before and after the intervention (P<0.01). The results demonstrated that concept mapping education enhances clinical decision-making. Therefore, this teaching method, which promotes students' reflection, creativity, and decision-making skills, is recommended in nursing education. Concept mapping is an effective, innovative, and cost-efficient educational strategy.